MDS Codes with Complementary Duals over Finite Fields - ABASSI, Nour El Houda; ALIANE, Khira Soulef; Supervisor: LEBED, Khawla (University of M'sila, 2023)
A linear complementary dual (LCD) code is a linear code C whose dual code C⊥ satisfies C u C⊥ = {0}. LCD codes have been used in certain communication systems. This application of LCD codes renewed the interest in the construction of LCD codes having a large minimum distance. Maximum Distance Separable MDS codes are a class of error correcting codes that achieve the maximum possible distance between code-words. Maximum distance separable with complementary dual (LCD MDS) codes are very important in coding theory and practice. We focus in this work on LCD MDS codes constructed from generalized Reed-Solomon (GRS) codes over finite fields
Keywords: Linear complementary dual (LCD), generalized Reed-Solomon (GRS) code , MDS code.